An Improved Repetitive Control for Circulating Current Restraining in MMC-MTDC - Yahui Wang; Yijia Cao; Yong Li; Chang Li (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The modular multilevel converter (MMC) is widely used in many important application fields such as high voltage DC transmission system. And the multi-terminal architecture of it attracts many attentions. However, the circulating current of MMC is an inherent problem which is mainly caused by the voltage mismatch between arms and DC bus. In this paper, an advanced repetitive control method is proposed. This method is based on the even-harmonic characteristic of the circulating current and the potential feature of repetitive control that it has an internal integration part. The pole diagram of the closed loop transform function of the proposed control system proves the stability of the proposed method. And according to the simulation results of a three-terminal MMC-MTDC model in PSCAD/EMTDC, the improved repetitive control presents better circulation repression ability and superior anti-interference capability by comparing with traditional PI control method. Additionally, the simulation results also indicate that the proposed repetitive controller can restrain the fluctuation of SM voltage more effectively than PI control.